2012
DOI: 10.1161/circulationaha.111.081059
|View full text |Cite
|
Sign up to set email alerts
|

Statins and the Risk of Cancer After Heart Transplantation

Abstract: Background— Although newer immunosuppressive agents, such as mTOR (mammalian target of rapamycin) inhibitors, have lowered the occurrence of malignancies after transplantation, cancer is still a leading cause of death late after heart transplantation. Statins may have an impact on clinical outcomes beyond their lipid-lowering effects. The aim of the present study was to delineate whether statin therapy has an impact on cancer risk and total mortality after heart transplantation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 62 publications
(54 reference statements)
1
30
0
Order By: Relevance
“…Since our results indicate simvastatin as an inhibitor of pathological lymphangiogenesis, it would be of interest to investigate whether cancer patients on statin therapy might have a better prognosis due to decreased tumor lymphangiogenesis and metastasis (3,6). Indeed, a recent publication indicates that patients on statin therapy develop fewer cancers and have a better prognosis once cancers have been diagnosed (44).…”
Section: Discussionmentioning
confidence: 81%
“…Since our results indicate simvastatin as an inhibitor of pathological lymphangiogenesis, it would be of interest to investigate whether cancer patients on statin therapy might have a better prognosis due to decreased tumor lymphangiogenesis and metastasis (3,6). Indeed, a recent publication indicates that patients on statin therapy develop fewer cancers and have a better prognosis once cancers have been diagnosed (44).…”
Section: Discussionmentioning
confidence: 81%
“…Ras, Rho, Rac) involved in the regulation of cellular processes including differentiation and apoptosis. These processes are germane to PAH (Connolly & Aaronson, 2011;Oka, Fagan, Jones, & McMurtry, 2008) and to cancer, where statins have been reported to reduce tumour growth and metastasis in patients following cardiac transplantation (Fröhlich et al, 2012). Prenylation of Rho proteins is essential for proper membrane localization, and appears to be required for most, but not all, known Rho functions.…”
Section: Statinsmentioning
confidence: 99%
“…There was no change in summary effect size with omitting 1 study at a time or fixedeffects model. The outcomes from studies by Fröhlich et al 9 (5/151) and Grigioni et al 20 (6/186) were not included in the pooled analysis because these 2 studies reported the rates of myopathy only in heart transplant recipients undergoing statin therapy.…”
Section: Myopathymentioning
confidence: 99%